1989
DOI: 10.1152/jappl.1989.66.1.336
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular response to cycle exercise during and after pregnancy

Abstract: Our purpose was to determine if pregnancy alters the cardiovascular response to exercise. Thirty-nine women [29 +/- 4 (SD) yr], performed submaximal and maximal exercise cycle ergometry during pregnancy (antepartum, AP, 26 +/- 3 wk of gestation) and postpartum (PP, 8 +/- 2 wk). Neither maximal O2 uptake (VO2max) nor maximal heart rate (HR) was different AP and PP (VO2 = 1.91 +/- 0.32 and 1.83 +/- 0.31 l/min; HR = 182 +/- 8 and 184 +/- 7 beats/min, P greater than 0.05 for both). Cardiac output (Q, acetylene reb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 0 publications
3
30
0
2
Order By: Relevance
“…During submaximal non-weight-bearing exercise, the difference in absolute VO 2 (L/min) between pregnant and nonpregnant women is either unchanged or increased during pregnancy. 12,26,[30][31][32][33][34][35][36][37] In contrast, during weight-bearing exercise the absolute VO 2 (L/min) is elevated further and has been suggested to be related to gestational weight gain. However, when these values are expressed relative to body weight (mL/kg/min) oxygen consumption is lower, similar or slightly higher for a given work rate.…”
Section: Energy Expenditure During Pregnancymentioning
confidence: 99%
“…During submaximal non-weight-bearing exercise, the difference in absolute VO 2 (L/min) between pregnant and nonpregnant women is either unchanged or increased during pregnancy. 12,26,[30][31][32][33][34][35][36][37] In contrast, during weight-bearing exercise the absolute VO 2 (L/min) is elevated further and has been suggested to be related to gestational weight gain. However, when these values are expressed relative to body weight (mL/kg/min) oxygen consumption is lower, similar or slightly higher for a given work rate.…”
Section: Energy Expenditure During Pregnancymentioning
confidence: 99%
“…This study also confirmed earlier findings that short duration, moderate intensity cycling is well-tolerated by the mother in either posture. 4,5,16 Most importantly, this is the first report demonstrating that FHR responses to cycling are posture-independent. There were no potentially adverse indicators, such as fetal bradycardia or FHR deceleration to suggest that the babies were at risk.…”
Section: Discussionmentioning
confidence: 71%
“…Compared with postpartum values, some studies found that cardiac output during pregnancy increases with upright cycling, 3,4 but not with semi-supine cycling. 5 Secondly, does semi-supine exercise have any potential advantages?…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy-induced effects on cardiovascular function are increases in heart rate (HR), stroke volume (SV), and cardiac output. [3,4] These changes result from the interactive effects of a primary reduction in peripheral vascular resistance, [5] cardiac autonomic modulation and barorefl ex function that lead to a higher resting heart rate.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy-induced effects on cardiovascular function are increases in heart rate (HR), stroke volume (SV), and cardiac output. [3,4] These changes result from the interactive effects of a primary reduction in peripheral vascular resistance, [5] cardiac autonomic modulation and barorefl ex function that lead to a higher resting heart rate.It is well established that high-frequency (HF) power (0.15-0.40 Hz) of HRV is mediated by parasympathetic nervous system (PNS) modulation and respiratory sinus arrhythmia, [6][7][8] whereas low-frequency (LF) power (0.03-0.15 Hz) refl ects both sympathetic nervous system (SNS) and parasympathetic nervous system (PNS) autonomic infl uences. [8,9] The ratio of low-frequency power to high-frequency power (LF/HF) has been used to refl ect cardiac sympathetic modulation (SNS…”
mentioning
confidence: 99%